Le péché originel xvie-xxe siècles L'impossible dogme au défi de la modernité - Hours, Bernard; Meyer, Frédéric; Milbach, Sylvain (Chrétiens et Sociétés. Documents et Mémoires, 2022)
Is original sin, which plays the basso continuo in the history of Christianity, an object of study for the historian? This is doubtful, given the bibliography, which is dominated by works by theologians and philosophers. However, it is a key dogma of Christianity that is of interest to the historian: in addition to the fact that a large part of sacramental practice is based on it, it brings into play a conception of humanity from which stems a conception of society and the social order, of evil, of suffering, of freedom, of men and women. It was between the eighteenth and late nineteenth centuries that the dogma came under the most radical criticism and that the debate on original sin changed its status: it was no longer simply the subject of doctrinal polemics between Catholics and Protestants. The dogma increasingly aroused repugnance and incomprehension: in scholarly opinion, drawing on new knowledge about man and nature, original sin went from being "not possible" to "no longer possible". Catholic apologetics had its work cut out defending the dogma. The coincidence between the slow exhaustion of its socially recognised meaning and the advent of a society of "opinions" cannot be reduced to the caricatural process of erasing a "legend". In addition to the historicity of the story of the Fall, the criticism also touches on the anthropological dimension of the dogma (the nature of evil) and its consequences in civilisational terms (the notion of progress). These two aspects are intimately linked and ultimately affect behaviour and the way humanity and society are represented.The loss of credit for original sin or its reinterpretations have favoured the thesis that the kingdom of God is possible on earth, and have legitimised a right to happiness and equality. We are talking about a genuine anthropological revolution that should precede a reconfiguration of the city of man. Didn't Baudelaire write: "Theory of true civilisation. It does not lie in gas, steam or turntables; it lies in reducing the traces of original sin"?